Medical Records Study: The Relationship between Pregnancy Complications with the Incidence of Low Birth Weight Baby at Ajibarang General Hospital - Yektiningtyastuti, Yektiningtyastuti; Amalia, Pety Valeri (Procedia of Engineering and Life Science, 2024)
Low Birth Weight (LBW) is a baby born with a weight of less than 2500 grams. Based on data from the Indonesian Health Profile (2020), LBW is the largest contributor (32%) to the cause of neonatal deaths. BPS Central Java Province data shows that in 2021 there were 22,240 babies born with LBW, while in Banyumas Regency the number of babies born with LBW was 1,629. Many factors are associated with the incidence of LBW, including complications during pregnancy. This medical record research aims to determine the relationship between pregnancy difficulties/complications and the incidence of LBW at Ajibarang General Hospital in 2022. The research design used a case-control study. The research was carried out from July to August 2023, with a sample of 146 newborn babies at Ajibarang General Hospital consisting of a case sample of 73 LBW babies (PO7.1), and a control sample of 73 babies born with normal weight (Z.38.0). The results of the study showed that of the 146 samples of newborns, 31.5% were born to mothers who experienced the pregnancy complication of preeclampsia (O14.9), gemelli (O30.0) 8.9%, premature rupture of membranes/PROM (O42.9) 30.1%, oligohydramnios (O41.0) 25.3%, and anemia (O99.0) 2.1%. The results of statistical tests show that there was a significant relationship between pregnancy complications and the birth of LBW babies, preeclampsia (p-value = 0.002, OR = 3.289), gemelli (p-value = 0.004, OR = 14.164), PROM (p-value =0.002, OR = 3.407), and oligohydramnios (p-value = 0.008, OR = 0.321). There is no significant relationship between anemia pregnancy complications and the incidence of LBW (p-value = 1.000).